Embedding the International Classification of Functioning, Disability and Health in Health Professions Curricula to Enable Interprofessional Education and Collaborative Practice. (August 2020) - Moran, Monica; Bickford, Jane; Barradell, Sarah; Scholten, Ingrid
The World Health Organization's International Classification of Functioning, Disability and Health (WHO-ICF) is a comprehensive and highly adaptable framework that provides a universal language and shared health concepts to articulate human functioning across the lifespan and from individual to population health settings. It provides a global, biopsychosocial, and holistic structure for conceptualising the human experience of health and health service provision. Consequently, the ICF framework offers hope for a universal map for health service providers that bridges professional, cultural, economic, and geographical variations. While the use of the ICF is typically mandated by health professions accreditation bodies, integration of the ICF in medical and health professional education programmes has been slow. In addition, its potential for scaffolding interprofessional education for collaborative practice has not been maximised. In this Perspective paper, we draw on our extensive experience in developing curricula and teaching within a range of health professions programmes (medicine, occupational therapy, physiotherapy, and speech-language pathology) to provide advice on conceptual, theoretical, and practical dimensions of embedding the ICF framework within curricula to support interprofessional education and collaborative practice.